The Struggle of Objects and Meaning: Design, Representation and Material Culture in the Everyday Objects of Orhan Pamuk's 'Museum of Innocence'. (2nd January 2017) - Timur Ogut, Sebnem
Abstract: Having been awarded the 2006 Nobel Prize for literature, Orhan Pamuk's next novel was entitled The Museum of Innocence . The novel, which bears the same name as an actual museum, is one of a kind, because before writing the novel he started to collect the items that would be described in the story, then, or simultaneously, he wrote the novel and opened a museum that consists of the objects depicted in the novel (Pamuk, 2008). He defines the novel as 'an annotated catalogue of the museum, relating in detail the stories of each and every object' (Pamuk, 2009: 702). This article sets out to explore, first on a semiotic level, the struggle between the objects and their meaning; secondly the dilemma between Lyotard's figural and discursive fields within the novel/museum; and finally, with regard to its implications for design, the significance of objects will be discussed in relation to everyday life and material culture studies, with an emphasis on memory and identity.